Solitary Sclerotic Fibroma - Rita Bouceiro-Mendes; M. Mendonça-Sanches; S. Antunes-Duarte; L. Soares- (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Sclerotic fibroma (SF) or storiform collagenoma is a rare and benign skin tumor. Clinically, it usually presents as an asymptomatic, slowly growing papule or nodule on the skin of the head, neck and upper extremities. Other locations have been described including the trunk, oral mucosa and nail bed. SF can present either as a solitary tumor or as multifocal cutaneous lesions and it may occur sporadically or in association with Cowden syndrome. Herein, we report a case of a solitary SF with typical clinical and histologic features, not associated with Cowden disease.